An updated checklist of Recent ostracods (Crustacea: Ostracoda) from inland waters of Sicily and adjacent small islands with notes on their distribution and ecology. Issue 1 (1st January 2020) - Pieri, V.; Marrone, F.; Martens, K.; Rossetti, G.
Abstract: Because of its position in the middle of the Mediterranea Sea and a complex geological history that has promoted repeated waves of biological colonization, Sicily (Southern Italy) is of particular interest from a biogeographical perspective. A number of previous investigations, dating back as far as the end of the 19 th century, have contributed to gather information about the occurrence of Recent non-marine ostracods in Sicily, making this region one of the most intensively studied areas of the Central Mediterranean. Published data on ostracod distributions have been integrated through an extensive field survey on mainland Sicily and surrounding small islands and archipelagos. Altogether, 271 ostracod samples and 11 sediment samples from dry water bodies were analysed from 218 sites visited between 2002 and 2017. Sampling sites were selected to encompass all the most common types of freshwater aquatic habitats, both natural and artificial, present in the area. Thirty-nine ostracods were identified at species level and 12 at supraspecific level. The present study reports four species ( Cypria subsalsa, Eucypris mareotica, Physocypria kerkyrensis, Vestalenula boteai ) and one genus ( Vestalenula ) as new for both peninsular Italy and adjacent islands, and three species ( Candonopsis novaezelandiae, Ilyocypris inermis, Neglecandona neglecta ) and two genera ( Candonopsis and Physocypria ) as new for Sicily. The updated checklist of the study area now includes at least 46 nominal species and other taxa identified at supraspecific level, belonging to 28 genera in 8 families (Candonidae, Cyprididae, Cytherideidae, Darwinulidae, Hemicytheridae, Ilyocyprididae, Limnocytheridae and Notodromadidae). The present investigation represents a significant addition to the knowledge of the ostracod diversity and distribution in the Sicilian area and in Italy as a whole. It also provides a sound baseline data for further comparative faunal studies aimed at investigating the affinities and origins of the central Mediterranean inland-water ostracod faunas, and to analyse their biogeographic patterns.